2019
DOI: 10.3168/jds.2018-15531
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Adipocyte sizes in the digital fat pad and their relationship to body condition in dairy cows

Abstract: Lameness and body condition are closely related. Recent studies have shown that cows with low body condition score (BCS) have a greater risk for developing lameness than cows with higher BCS. Among other reasons, this relationship might be related to the reduced thickness of the digital fat cushion in lean cows. The digital cushion is not a homogeneous structure but consists of different fat pads and connective tissue. We hypothesized that either high or low BCS will result in concordant adipocyte sizes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…This study found that adipocyte cell size was significantly larger in animals with a higher BCS. This is consistent with a previous study that investigated adipocyte size in bovine right front claws in cows with a BCS of less than 3.00, and 3.00 or more, on a 1 to 5 scale (Hiss-Pesch et al, 2019), a study which also supports our assertion that the digital cushion is not a homogeneous tissue. Interestingly, the average adipocyte cell size in the current study (between 373 and B) Body condition score grouped into scores of 1.50 to 2.50 (n = 8) and 3.00 to 4.00 (n = 7; P > 0.05 independent samples t-test).…”
Section: Anatomical and Cellular Structure Of The Digital Cushionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study found that adipocyte cell size was significantly larger in animals with a higher BCS. This is consistent with a previous study that investigated adipocyte size in bovine right front claws in cows with a BCS of less than 3.00, and 3.00 or more, on a 1 to 5 scale (Hiss-Pesch et al, 2019), a study which also supports our assertion that the digital cushion is not a homogeneous tissue. Interestingly, the average adipocyte cell size in the current study (between 373 and B) Body condition score grouped into scores of 1.50 to 2.50 (n = 8) and 3.00 to 4.00 (n = 7; P > 0.05 independent samples t-test).…”
Section: Anatomical and Cellular Structure Of The Digital Cushionsupporting
confidence: 93%
“…(C) Age grouped into 2 to <4 yr (n = 5) and ≥4 to 6.5 yr (n = 12; P > 0.05 independent samples t-test). 6248 759 µm 2 for each individual animal), was smaller in comparison to other publications on bovine species, where digital cushion adipocyte averages were between 1,426 and 5,692 µm 2 depending on the breed, location of the sample, and factors such as BCS (Hiss-Pesch et al, 2019). Adipocytes in subcutaneous and retroperitoneal adipose tissues reached around 7,000 and 8,000 µm 2 (Kénéz et al, 2015), whereas another study showed that subcutaneous and visceral depots had adipocyte cell areas ranging from 4,521 to 7,945 µm 2 (Akter et al, 2011).…”
Section: Anatomical and Cellular Structure Of The Digital Cushionmentioning
confidence: 58%
“…The inconsistency regarding when in lactation the SSTT nadir occurs between our study and the Newsome et al ( 17 ) study could be due to the difference in the fat pad targeted. A recent short communication by Hiss-Pesch et al ( 25 ) reported that the fat pads within the digital cushion are not uniform and that fat could be mobilized from them at different rates. It could also be due to different farm management systems or differences in genetics.…”
Section: Discussionmentioning
confidence: 99%
“…The KCNQ3 gene has previously been associated with milk fat percentage and milk yield in Holsteins (Kolbehdari et al, 2008;Jiang et al, 2019), while EFR3A has previously been associated with subclinical ketosis, milk fat percentage, and milk fatty acid composition in Holsteins (Li et al, 2014;Jiang et al, 2019;Soares et al, 2021). The lipid composition of the digital cushion changes with age (Räber et al, 2006) and is correlated with body condition (Hiss-Pesch et al, 2019;Newsome et al, 2021). Although it is not clear how the composition of the digital cushion affects its physical properties, it is plausible that the same genes that affect the fat and fatty acid content of milk could similarly influence the digital cushion.…”
Section: Key Results and Interpretation: Qtl Mappingmentioning
confidence: 99%